Antidermatophytic effect of Bacillus mojavensis SZMC 22228 and its secreted chymotrypsin-like protease - Galgóczy, László; Guba, Melinda; Sajben, Enikő; Vörös, Mónika; Takó, Miklós; Tserennadmid, Rentsenkhand; Vágvölgyi, Csaba (Acta Biologica Szegediensis, 2014)
The aim of the present study was to investigate the antifungal effect of Bacillus mojavensis SZMC 22228 against different dermatophytes and to isolate the antidermatophytic compound from the bacterial ferment broth. B. mojavensis SZMC 22228 and its cell-free ferment broth effectively inhibited the growth of clinical reference strain of Microsporum canis, Microsporum gypseum, Trichophyton mentagrophytes, Trichophyton rubrum and Trichophyton tonsurans in agar diffusion test in vitro. An antidermatophytic, 25 kDa protein (B. mojavensis SZMC 22228 antidermatophyitc protein, BMAP) was purified from the antifungally active, cell-free ferment broth using size exclusion and ion-exchange chromatography. BMAP showed antifungal effect against all of the investigated dermatophytes both in agar diffusion and broth microdilution susceptibility tests. M. gypseum proved to be the most susceptible dermatophyte to BMAP (MIC=40 μg/ml), all the other investigated fungi were less susceptible (MIC=80 μg/ml). The enzymatic activity of this protein was investigated in microtiter plate assay using hydrolase specific chromogenic substrates. BMAP showed high proteolytic activity towards N-Succ-Ala-Ala-Pro-Phe-pNA, and proved to be a chymotrypsin-like protease. These results suggest that the antidermatohytic activity of B. mojavensis SZMC 22228 correlates with its chymotrypsin-like protease production. After further investigations, the purified BMAP could be a promising base of a novel antidermatophytic strategy.